Inhibition of diacylglycerol lipase β modulates lipid and endocannabinoid levels in the ex vivo human placenta - Berger, Natascha; van der Wel, Tom; Hirschmugl, Birgit; Baernthaler, Thomas; Gindlhuber, Juergen; Fawzy, Nermeen; Eichmann, Thomas; Birner-Gruenberger, Ruth; Zimmermann, Robert; van der Stelt, Mario; Wadsack, Christian (Frontiers in Endocrinology, 2023)
The growing fetus and with it the placenta rely on an appropriate amount of lipids and fatty acids for developmental and metabolic processes. Placental dyslipidemia and aberrant activity of lipases have been linked to diverse pregnancy associated complications, such as preeclampsia and preterm birth. The two serine hydrolases, diacylglycerol lipase α and β (DAGLα, DAGLβ), catalyze the degradation of diacylglycerols leading to the formation of monoacylglycerols (MAG), including the endocannabinoid 2-arachidonoylglycerol (2-AG). The major role of DAGL in the biosynthesis of 2-AG is evident from various studies in mice but has not been investigated in the human placenta. In this study, we investigated the role of DAGL in placental lipid metabolism using selective inhibitors and activity-based protein profiling to generate a landscape of placental serine hydrolases. Thereby we show that the expression and activity of DAGLβ prevails in placental tissue, compared to DAGLα and that the enzyme is mainly located to trophoblasts. In an ex vivo placental perfusion approach, pharmacological inhibition of DAGLβ by the small molecule inhibitor DH376 led to reduced MAG tissue levels, including 2-AG. This indicates a major role of DAGLβ activity for determining 2-AG biosynthesis. Our study highlights that the activity of enzymes controlling placental lipid networks may trigger bioactive lipid signaling at the maternal-fetal interface with implications for placental function in normal and compromised pregnancies.